Analisis Kinerja Keuangan Dengan Metode Common Size Pada PT. Bank Mandiri (Persero) TBK - Jemi Pabisangan Tahirs (Peneliti.net, 2022)
The purpose of the study was to determine the composition of assets, liabilities and total income in the financial statements of PT. Bank Mandiri (Persero) Tbk using the Common Size method. The type of research in this research is quantitative research. The data used is secondary data, namely financial statements in the form of balance sheets and income statements for 2018-2020. The results showed that the balance sheet, especially assets, increased, but on the cash side it decreased. Liabilities, especially liabilities, experienced instability from 2018-2020. Equities are also experiencing instability. This shows that the bank's financial development is unstable, where the proportion of liabilities is greater than the proportion of equity. While on the income statement, seen from other operating income experiencing instability and profit for the year decreased in 2018-2020, this shows that the performance of PT. Bank Mandiri (Persero) Tbk in 2018-2020 was not good because the company was not able to maintain its net profit in the following year